Observer perspective imagery with stuttering. (October 2015) - Lowe, Robyn; Menzies, Ross; Packman, Ann; O'Brian, Sue; Onslow, Mark
Abstract Purpose: Adults who stutter are at risk of developing a range of psychological conditions. Social anxiety disorder is the most common anxiety disorder associated with stuttering. Observer perspective imagery is one cognitive process involved in the maintenance of some anxiety disorders. This involves viewing images as if looking at the self from the perspective of another. In contrast, the field perspective involves looking out from the self at the surrounding environment. The purpose of this study was to assess the presence of observer perspective imagery with stuttering. Method: The authors administered the Hackmann, Surawy and Clark (1998) semi-structured interview to 30 adults who stutter and 30 controls. Group images and impressions were compared for frequency, perspective recalled and emotional valence. Result: The stuttering group was significantly more likely than controls to recall images and impressions from an observer rather than a field perspective for anxious situations. Conclusion: It is possible the present results could reflect the same attentional processing bias that occurs with anxiety disorders in the non-stuttering population. These preliminary results provide an explanation for the persistence of conditions such as social anxiety disorder with stuttering. Clinical implications are discussed.